Apathetic symptoms and white matter integrity after traumatic brain injury. (29th July 2021) - Navarro-Main, B; Castaño-León, AM; Hilario, A; Lagares, A; Rubio, G; Periañez, JA; Rios-Lago, M; , INERTIA group collaborators
ABSTRACT: Primary objective: The aim of the study was twofold. First, to study the relationship among apathy in the long term, initial clinical measures, and standard outcome scores after traumatic brain injury (TBI). Second, to describe white matter integrity correlates of apathy symptoms. Research Design: Correlational study. Methods and Procedures: Correlation and Bayesian networks analyses were performed in a sample of 40 patients with moderate to severe TBI in order to identify the relationship among clinical variables, functionality, and apathy. A diffusion tensor imaging study was developed in 25 participants to describe correlations between fractional anisotropy (FA) measures and apathetic symptoms. Main outcomes and results: Correlation analysis revealed associations between pairs of variables as apathy in the long term and functional score at discharge from hospital. Bayesian network illustrated the relevant role of axonal injury mediating the relationship between apathy and initial clinical variables. FA in the superior longitudinal fasciculus, the inferior longitudinal fasciculus, and the internal capsule were negatively correlated with apathy measures. Widespread brain areas showed positive correlations between FA and apathy. Conclusions: These results highlight the relevance of white matter integrity measures in initial assessment after TBI and its relationship with apathetic manifestations in the chronic phase.